The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.30736/jpensi.v7i2.1055
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Managerial Ownership and Company Growth on Company Value through Institutional Ownership as a Moderation Variable

Abstract: This study aims to find out how much the discussion of Company Value through Institutional Ownership as a moderation variable: Managerial Ownership and Company Growth (In Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2016-2020). Data collection methods through ICMD and IDX sites and literature studies. The method of analysis used is regression analysis. The results of this study were obtained: (1) Managerial Ownership partially affects the Value of the Company (2) Company Growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies find a negative impact of managerial ownership on FP (e.g., Martha and Rina, 2023;Waseem et al, 2023;Saniyah and Azmi, 2022). Conversely, other studies have indicated that there is a positive impact of managerial ownership on FP (e.g., Nurjanah, 2022;Yudha et al, 2022;Djanor and Erawati, 2022). Furthermore, some studies show that managerial ownership has no impact on FP (e.g., Fauziah and Winarso, 2023;Elia et al, 2022;Florackis et al, 2020;Risa et al, 2022).…”
Section: ‫ال‬ ‫مجلة‬ ‫المحاسبية‬ ‫بحوث‬mentioning
confidence: 89%
“…Some studies find a negative impact of managerial ownership on FP (e.g., Martha and Rina, 2023;Waseem et al, 2023;Saniyah and Azmi, 2022). Conversely, other studies have indicated that there is a positive impact of managerial ownership on FP (e.g., Nurjanah, 2022;Yudha et al, 2022;Djanor and Erawati, 2022). Furthermore, some studies show that managerial ownership has no impact on FP (e.g., Fauziah and Winarso, 2023;Elia et al, 2022;Florackis et al, 2020;Risa et al, 2022).…”
Section: ‫ال‬ ‫مجلة‬ ‫المحاسبية‬ ‫بحوث‬mentioning
confidence: 89%